EMOTIONAL DIMENSIONS IN LAND ACQUISITION NEGOTIATION: INSIGHTS FROM A BRAZILIAN CASE - Murillo de Oliveira Dias; Raphael de Oliveira Albergarias Lopes; Thiago Schmitz (American Journals Publishing, 2026)
The research article examines civil engineering land acquisition negotiations using qualitative case study methods, showing how emotional connections between parties affect their negotiation strategies. The landowner's strong emotional bond to his property led to a sale price exceeding market value, creating a conflict between his rational assessment of the property and his emotional valuation. The research demonstrates that organizations implemented structural innovations through Special Purpose Entities (SPEs), non-monetary options, and financial safeguards to generate value as they evolved from distributive bargaining to integrative negotiation. The research findings show that organizations must address both physical and psychological factors, as they demonstrate that successful teamwork is achieved through readiness combined with relationship development, using objective assessment techniques.
Keywords: Negotiation; Civil Engineering Case Study; Integrative Strategies